Assessing the Dimensional Validityand Reliability of the University of Florida Critical Thinking Inventory (UFCTI) in Chinese: A Confirmatory Factor Analysis - Matt Baker; Peng Lu; Alexa J. Lamm (Journal of International Agricultural and Extension Education, 2021)
The importance of assessing critical thinkinghas been emphasized extensively by numerous administrators and educatorsin higher education worldwide. In a contemporary agricultural sustainable development environment, agricultural students need to develop critical thinkingto manage complex situations and to deal with controversial issues in international agriculture settings.From psychological points of view, thinking varies cross-culturally. In other words, people from different cultures think differently. With the increasing number of Chinese students studying in the U.S., educators need to be aware of the importance of supporting these Chinese students within the intercultural classroom environment. Thus, it is necessaryto explore and understand the way Chinese students thinkto help them more easily adapt to a culturally diverse educational environment.The purpose of this study wasto evaluate the validity and reliability of a Chinese version of the University of Florida Critical Thinking Inventory (UFCTI). The UFCTI measures critical thinkingstyles using two constructs: engagement and seeking information. Confirmatory FactorAnalysis (CFA) was applied to examine thehypothesized measurement model based on the theoretical foundations of the original UFCTI (English version). The CFA findings indicated the UFCTI measurement model between the two versions is equivalent. Specifically, the results confirmed the two-factormeasurement ofcritical thinking style: engagement and seeking information. The findings also indicatedadequatevalidity and reliability for the UFCTI Chinese version
Keywords: critical thinking style; Chinese students; confirmatory factor analysis; agricultural education